2007
DOI: 10.3748/wjg.v13.i20.2862
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of vascular endothelial growth factor production and its effect on revascularization and function of graft islets in diabetic rats

Abstract: AIM:To determine whether the elevated vascular endothelial growth factor (VEGF) expression produced by the transfected vascular endothelial cells (VECs) could stimulate angiogenesis of the graft islets and exert its effect on the graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
“…Trying to increase the blood supply of the graft soon after implantation, Cheng et al (5) have injected vascular endothelial cells L and vascular endothelial growth factor (VEGF) to stimulate angiogenesis. The use of growth factors was made of in other works too (5,33,62) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies found that CTGF can induce the production of basement membrane components, such as collagen and fibronectin cularization and maintaining the vascular permeability of the rat grafted islets [68]. Upregulation of VEGF accelerates islet revascularization, which increases the survival of transplanted islets [69]. Experiments have shown that VEGF knocked-out mice contain defective remaining capillaries.…”
Section: Connective Tissue Growth Factormentioning
confidence: 99%
“…Such approaches are expected to ensure adequate microvascular perfusion to islet cells and protect implanted islet cells from hypoxia-induced inflammation and necrosis, which will ultimately improve the outcome of islet transplantation by reducing the donor/recipient ratio thus increasing the success rate of islet transplantation [28]. Antioxidant supplementation [29,68], elevation of vascular endothelial growth factor (VEGF) delivery [30] to islet grafts and co-transplantation of bone marrow-derived mesenchymal stem cells [31] improves the outcome of islet transplantation by enhancing islet revascularization.…”
Section: Islet Transplantationmentioning
confidence: 99%